Press in System of Bolshevik Propaganda during the Civil War in the North-West of Russia in 1919 - A. A. Konkin; I. A. Tropov (Научный диалог)
The issues related to determining the place of the regional Bolshevik press in the system of propaganda activities of the Bolsheviks during the Civil War in the North-West of Russia in 1919 are discussed in the article. The relevance of the study is due to the significant role of the media in the regulation of socio-political processes both in modern Russia and in its historical past. The novelty of the study is in the consideration of the Bolshevik periodicals as a purposefully used by the "red" tool in achieving victory in the military-political confrontation with the White Guards. A comparative analysis of the materials of Bolshevik publications published in 1919 in the North-West of Russia was carried out. It is concluded that the press occupied an important place in the Bolshevik propaganda system in the northwestern region. It was established that its keynote was the formation of a negative image of the enemy in contrast with the Bolsheviks and the Red Army. It is proved that in the local Bolshevik press the image of "Soviet power" as the only fair and the Red Army as a powerful and invincible force was consistently created. It is shown that the positions and slogans put forward in the Bolshevik press were called upon to provide massive support for the revolutionary forces in the region and the mobilization of forces to repulse the enemy.